Major difficulties in the work of a tutor with a team of students within the tame international project - Patsera, M. V.; Skrypnykova, Y. S.; Пацера, Марина Вікторівна; Скрипникова, Яніна Семенівна (Запорізький державний медичний університет, 2018)
Modern conditions for knowledge acquisition dictate the need for intensification of education and search for new pedagogical approaches to the training of students at higher medical institutions. One of these new approaches is the TAME (Training Against Medical Error) project within the framework of the Erasmus+ grant program. The major feature of this educational project is studying the material not on a certain topic, but in a multidisciplinary way, through a "virtual patient".
Keywords: TAME international project; student; virtual patient; tutor